Naïve realism and diaphaneity - French, Craig (Oxford University Press, 2018)
Naïve Realists think that the ordinary mind-independent objects that we perceive are constitutive of the character of experience. Some understand this in terms of the idea that experience is diaphanous: that the conscious character of a perceptual experience is entirely constituted by its objects. My main goal here is to argue that Naïve Realists should reject this, but I’ll also highlight some suggestions as to how Naïve Realism might be developed in a non-diaphanous direction.